النشاط البدني الرياضي المكيف ودوره في تنمية المهارات الحركية للطفل المصاب بمتلازمة داون دراسة ميدانية –جمعية عصافير الجنة -صالح باي- - دريعي ، حمزة; Supervisor : شاكر ، بلواضح (Mohamed Boudiaf University of M'Sila, 2025)
الملخص: تهدف هذه الدراسة إلى التعرف على دور النشاط البدني الرياضي المكيف في تطوير المهارات الحركية لدى الأطفال المصابين بـمتلازمة داون، وذلك من خلال استخدام المنهج الوصفي بالاعتماد على أدوات البحث المناسبة كالملاحظة والاستبيان. وقد تم اختيار عينة قصدية من الأطفال المنتسبين إلى جمعية عصافير الجنة بدار الشباب الشهيد كعبش عبد الله صالح باي. تم التطرق في الجانب النظري إلى مفاهيم أساسية كالنشاط البدني المكيف، المهارات الحركية، وخصائص متلازمة داون، أما في الجانب التطبيقي فتم التركيز على دراسة تأثير بعض الأنشطة الحركية على تطور التوازن، التناسق العضلي، والقدرة الحركية. وقد توصلت الدراسة إلى أن ممارسة الأنشطة البدنية الموجهة تساهم بفعالية في تحسين القدرات الحركية لهؤلاء الأطفال، كما تلعب دورًا في تعزيز ثقتهم بأنفسهم واندماجهم الاجتماعي، مما يجعل النشاط البدني أداة فعالة في التكفل الشامل بذوي متلازمة داون. عنوان الدراسة: النشاط البدني الرياضي المكيف ودوره في تنمية المهارات الحركية للطفل المصاب بمتلازمة داون دراسة ميدانية –جمعية عصافير الجنة -صالح باي- أهداف الدراسة:  التعرف على الإطار النظري والعلمي لمتلازمة داون من حيث أسبابها، خصائصها الجسدية والعقلية،وتأثيرها على النمو الحركي للأطفال.  توضيح مفهوم النشاط البدني الرياضي المكيف من حيث أسسه النظرية، أهدافه، مبادئه وخصائص برامجه التأهيلية.  تحليل تأثير النشاط البدني الرياضي المكيف في تنمية مهارة القفز لدى الأطفال المصابين بمتلازمة داون من خلال تعزيز قوة الأطراف السفلية وتحسين التناسق العضلي العصبي.  دراسة دور النشاط البدني الرياضي المكيف في تحسين مهارة الجري، خاصة من حيث التوازن الديناميكي، ضبط الحركة والتناسق الحركي العام.  إبراز أثر النشاط البدني الرياضي المكيف في تحسين مهارة التوازن الثابت والديناميكي لدى الأطفال المصابين بمتلازمة داون باعتبار التوازن من أبرز الصعوبات الحركية لديهم.  تقييم فعالية البرامج الرياضية المكيفة في تنمية مهارة القذف من خلال تحسين التنسيق العضلي العلوي، والتحكم الحركي في الأطراف العلوية.  المساهمة في تقديم مقترحات عملية قائمة على الأسس العلمية قد تفيد المختصين في التربية البدنية والتأهيل الحركي في إعداد برامج رياضية موجهة للأطفال المصابين بمتلازمة داون.  تسليط الضوء على ضرورة التكفل المبكر والنوعي بهذه الفئة من خلال دمج النشاط البدني في البرامج التربوية والعلاجية لتعزيز فرصهم في التكيف الاجتماعي والاستقلالية الوظيفية. التساؤل العام الدراسة: ما هو دور النشاط البدني الرياضي المكيف في تطوير المهارات الحركية لدى الأطفال المصابين بمتلازمة داون؟ التساؤلات الجزئية: 1) هل للنشاط البدني الرياضي المكيف دور في تطوير مهارة القفز لدى الأطفال المصابين بمتلازمة داون؟ 2) هل للنشاط البدني الرياضي المكيف دور في تطوير مهارة الجري لدى الأطفال المصابين بمتلازمة داون؟ 3) هل للنشاط البدني الرياضي المكيف دور في تطوير مهارة التوازن لدى الأطفال المصابين بمتلازمة داون؟ 4) هل للنشاط البدني الرياضي المكيف دور في تطوير مهارة القذف لدى الأطفال المصابين بمتلازمة داون؟ الفرضية العامة للدراسة: للنشاط البدني الرياضي المكيف دور إيجابي وفعّال في تطوير وتنمية المهارات الحركية المختلفة لدى الأطفال المصابين بمتلازمة داون. الفرضيات الجزئية • للنشاط البدني الرياضي المكيف دور فعّال في تطوير مهارة القفز لدى الأطفال المصابين بمتلازمة داون من خلال تحسين القوة العضلية للأطراف السفلية وتعزيز التنسيق الحركي. • يساهم النشاط البدني الرياضي المكيف في تحسين مهارة الجري لدى الأطفال المصابين بمتلازمة داون من خلال تعزيز التوازن الديناميكي وضبط الحركة وسلاسة التنقل. • للنشاط البدني الرياضي المكيف دور جوهري في تحسين مهارة التوازن الثابت والديناميكي لدى الأطفال المصابين بمتلازمة داون من خلال تقوية الجهاز العصبي العضلي وتحسين الاستجابة الحركية. • يسهم النشاط البدني الرياضي المكيف في تنمية مهارة القذف لدى الأطفال المصابين بمتلازمة داون من خلال تطوير التحكم الحركي الدقيق وتحسين القوة العضلية للأطراف العلوية. المنهج المتبع في الدراسة: المنهج في البحث العلمي عبارة عن مجموعة من القواعد والأسس وظفت من أجل الوصول إلى الحقيقة، يختلف هذا الأخر اختلاف المواضيع المدروسة. اعتمدت هذه الدراسة على المنهج الوصفي التحليلي، كونه الأنسب لدراسة الظواهر الاجتماعية والتربوية والإنسانية التي لا تتطلب إجراء تجارب مخبرية مباشرة، وإنما تعتمد على جمع المعلومات وتحليلها وتفسيرها من خلال المصادر النظرية والدراسات السابقة ذات الصلة بالموضوع. وقد تم اختيار هذا المنهج باعتباره الأداة العلمية الملائمة لفهم وتحليل دور النشاط البدني الرياضي المكيف في تطوير المهارات الحركية لدى الأطفال المصابين بمتلازمة داون. الأدوات المستخدمة في الدراسة: لأجل إجراء هذه الدراسة ونظرا لطبيعة عينة الدراسة قام الباحث باستخدام الأدوات التالية: الاستبيان: عبارة عن مجموعة من الأسئلة تدور حول موضوع معين تقدم لعينة من الأفراد للإجابة عنها وتعد هذه الأسئلة في شكل واضح بحيث لا تحتاج لشرح إضافي. تربص ميداني: على مستوى دار الشباب كعبش عبد الله أين يقع مقر جمعية عصافير الجنة. الكلمات المفتاحية بالعربية النشاط البدني المكيف – المهارات الحركية – متلازمة داون – الإعاقة العقلية – التربية البدنية الخاصة. بالإنجليزية: Adapted physical activity – Motor skills – Down syndrome – Intellectual disability – Special physical education. جاء هذا البحث في ستة فصول: الفصل الأول: الإطار العام للدراسة. الفصل الثاني: النشاط البدني المكيّف. الفصل الثالث: المعاقيــن ذهنيا ومتلازمــة داون. الفصل الرابع: منهجية الدراسة. الفصل الخامس: عرض وتحليل ومناقشة النتائج. الفصل السادس: الاستنتاجات والاقتراحات. أهم التوصيات 1) العمل على إدماج برامج النشاط البدني المكيف ضمن البرامج التربوية الرسمية لجميع مراكز التربية الخاصة والجمعيات التي تعنى بالأطفال المصابين بمتلازمة داون. 2) تكوين أخصائيين في النشاط البدني المكيف من خلال برامج أكاديمية ودورات تدريبية متخصصة، تُمكنهم من التعامل العلمي والتربوي مع الأطفال ذوي الاحتياجات الخاصة. 3) ضرورة اعتماد فرق متعددة التخصصات (طبيب مختص، أخصائي نفسي حركي، أخصائي علاج وظيفي، مربي رياضي، أخصائي نفسي تربوي، أخصائي تغذية...) للعمل بشكل منسق على تطوير الأداء الحركي والمعرفي والنفسي لهؤلاء الأطفال. 4) تطوير أدوات تقييم دورية لمتابعة مدى فعالية البرامج الحركية المطبقة وتعديلها حسب احتياجات كل حالة. 5) تشجيع البحث العلمي المحلي والعربي في مجال النشاط البدني المكيف من خلال توفير الدعم المادي والمعنوي للباحثين. 6) تخصيص قاعات وتجهيزات رياضية متخصصة مزودة بوسائل حديثة تسمح بتنفيذ الأنشطة الحركية الموجهة بطريقة آمنة وفعالة للأطفال المصابين بمتلازمة داون. 7) تفعيل دور الأسرة عبر تنظيم ورشات تكوين وتدريب للأولياء لتمكينهم من مواكبة تطبيق التمارين مع أبنائهم في المنزل. Institute : Science and Techniques of Physical and Sports Activities Department: Adapted Physical and Sports Activity Serial Number: .............................................................................................................................. Registration Number: .................................................................................................................... Student: Driai Hamza Date of Defense: 02/10/2025 Thesis Title: « Adapted Physical and Sports Activity and Its Role in Developing Motor Skills in Children with Down Syndrome » A Field Study – “Oiseaux du Paradis” Association – Salah Bey Thesis Language: Arabic Thesis Type: Master’s Degree Country: People’s Democratic Republic of Algeria – Wilaya of M’sila University: “Mohamed Boudiaf” University of M’sila Supervisor: Dr. Chaker Belouadhah Number of Pages: 64 Electronic File: (Word / PDF) Field of Study: Adapted Physical and Sports Activity Specialty: Adapted Physical and Sports Activity and Health Abstract: This study aims to identify the role of adapted physical and sports activity in developing motor skills among children with Down syndrome. The descriptive method was used, relying on appropriate research tools such as observation and questionnaires. A purposive sample was selected from children affiliated with the “Oiseaux du Paradis” Association at the Martyr Kaabach Abdallah Youth Center in Salah Bey. The theoretical part of the study addressed key concepts such as adapted physical activity, motor skills, and the characteristics of Down syndrome. The practical part focused on examining the effects of specific motor activities on the development of balance, muscular coordination, and motor ability. The results revealed that engaging in guided physical activities significantly contributes to improving the motor abilities of these children. Moreover, it enhances their self-confidence and social integration, confirming that adapted physical activity is an effective tool for the comprehensive care of individuals with Down syndrome. Study Title: Adapted Physical and Sports Activity and Its Role in Developing Motor Skills in Children with Down Syndrome A Field Study – “Oiseaux du Paradis” Association – Salah Bey Study Objectives: • To identify the theoretical and scientific framework of Down syndrome in terms of its causes, physical and mental characteristics, and its effects on children’s motor development. • To clarify the concept of adapted physical and sports activity with regard to its theoretical foundations, objectives, principles, and characteristics of its rehabilitation programs. Additional Objectives: • To analyze the impact of adapted physical and sports activity on the development of jumping skills among children with Down syndrome by enhancing lower-limb strength and improving neuromuscular coordination. • To study the role of adapted physical and sports activity in improving running skills, particularly in terms of dynamic balance, movement control, and overall motor coordination. • To highlight the effect of adapted physical and sports activity on improving both static and dynamic balance in children with Down syndrome, considering that balance represents one of their most prominent motor challenges. • To evaluate the effectiveness of adapted sports programs in developing throwing skills through the improvement of upper-limb muscular coordination and motor control. • To contribute practical, scientifically grounded recommendations that may assist specialists in physical education and motor rehabilitation in designing adapted sports programs for children with Down syndrome. • To emphasize the importance of early and specialized intervention for this group by integrating physical activity into educational and therapeutic programs, in order to enhance their chances of social adaptation and functional independence. Specific Research Questions: 1. Does adapted physical and sports activity play a role in developing jumping skills among children with Down syndrome? 2. Does adapted physical and sports activity play a role in developing running skills among children with Down syndrome? 3. Does adapted physical and sports activity play a role in developing balance skills among children with Down syndrome? 4. Does adapted physical and sports activity play a role in developing throwing skills among children with Down syndrome? General Research Hypothesis: Adapted physical and sports activity has a positive and effective role in developing and enhancing various motor skills in children with Down syndrome. Specific Research Hypotheses: • Adapted physical and sports activity plays an effective role in developing jumping skills among children with Down syndrome by improving lower-limb muscular strength and enhancing motor coordination. • Adapted physical and sports activity contributes to improving running skills in children with Down syndrome by enhancing dynamic balance, movement control, and fluidity of motion. • Adapted physical and sports activity plays a fundamental role in improving both static and dynamic balance skills in children with Down syndrome by strengthening the neuromuscular system and enhancing motor response. • Adapted physical and sports activity contributes to the development of throwing skills in children with Down syndrome by improving fine motor control and upper-limb muscular strength. Research Methodology: In scientific research, a methodology consists of a set of rules and principles employed to reach the truth, and it varies depending on the subject under study. This study adopted the descriptive-analytical method, as it is the most appropriate for examining social, educational, and human phenomena that do not require direct laboratory experiments. Instead, it relies on collecting, analyzing, and interpreting information from theoretical sources and previous studies related to the topic. This method was chosen as the most suitable scientific tool to understand and analyze the role of adapted physical and sports activity in developing motor skills among children with Down syndrome. Research Tools: For the purpose of this study, and considering the nature of the sample, the researcher used the following tools: • Questionnaire: A set of questions about a specific topic presented to a sample of individuals to answer. These questions were designed clearly so that no additional explanation was needed. • Field Training (Practical Internship): Conducted at the Kaabach Abdallah Youth Center, where the headquarters of the “Oiseaux du Paradis” Association is located. Keywords: Adapted Physical Activity – Motor Skills – Down Syndrome – Intellectual Disability – Special Physical Education. This research is organized into six chapters: • Chapter One: General Framework of the Study • Chapter Two: Adapted Physical Activity • Chapter Three: Individuals with Intellectual Disabilities and Down Syndrome • Chapter Four: Research Methodology • Chapter Five: Presentation, Analysis, and Discussion of Results • Chapter Six: Conclusions and Recommendations Key Recommendations: 1. Integrate adapted physical activity programs into official educational curricula for all special education centers and associations that serve children with Down syndrome. 2. Train specialists in adapted physical activity through academic programs and specialized training courses, enabling them to interact with children with special needs in a scientific and educational manner. 3. Establish multidisciplinary teams (including a medical specialist, psychomotor therapist, occupational therapist, sports educator, educational psychologist, nutritionist, etc.) to work in a coordinated way to develop the motor, cognitive, and psychological performance of these children. 4. Develop periodic assessment tools to monitor the effectiveness of implemented motor programs and adjust them according to the needs of each child. 5. Encourage local and regional scientific research in the field of adapted physical activity by providing material and moral support to researchers. 6. Allocate specialized halls and sports facilities equipped with modern tools that allow for the safe and effective implementation of guided motor activities for children with Down syndrome. 7. Activate the role of the family by organizing training workshops for parents, enabling them to support the implementation of exercises with their children at home.
Keywords: النشاط البدني المكيف; المهارات الحركية; متلازمة داون